2004
DOI: 10.1038/nsmb874
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the polysialic acid–degrading endosialidase of bacteriophage K1F

Abstract: Phages infecting the polysialic acid (polySia)-encapsulated human pathogen Escherichia coli K1 are equipped with capsule-degrading tailspikes known as endosialidases, which are the only identified enzymes that specifically degrade polySia. As polySia also promotes cellular plasticity and tumor metastasis in vertebrates, endosialidases are widely applied in polySia-related neurosciences and cancer research. Here we report the crystal structures of endosialidase NF and its complex with oligomeric sialic acid. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
233
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(242 citation statements)
references
References 50 publications
7
233
2
Order By: Relevance
“…2) shows two clearly distinct domains, the fully folded triple-β-helix stalk and the chaperone domain. The stalk domain essentially adopts the fold of an intertwined triple β-helix, which was previously described 7 , whereas the chaperone domain adopts the same architecture found for GP12-CIMCD (see above). A central twisted three-helix bundle (α4) of 35 Å length, surrounded by α-helices and two short antiparallel β-strands (α1-β1-α2-β2-α3-α3a) forms the core with an approximate diameter of 50 Å.…”
Section: A R T I C L E S a R T I C L E Ssupporting
confidence: 56%
See 2 more Smart Citations
“…2) shows two clearly distinct domains, the fully folded triple-β-helix stalk and the chaperone domain. The stalk domain essentially adopts the fold of an intertwined triple β-helix, which was previously described 7 , whereas the chaperone domain adopts the same architecture found for GP12-CIMCD (see above). A central twisted three-helix bundle (α4) of 35 Å length, surrounded by α-helices and two short antiparallel β-strands (α1-β1-α2-β2-α3-α3a) forms the core with an approximate diameter of 50 Å.…”
Section: A R T I C L E S a R T I C L E Ssupporting
confidence: 56%
“…Furthermore, it could be shown that some of the chaperone domains are exchangeable between the different preproteins 5,6 . While the three-dimensional structures of the CIMCDs are as yet unknown, the crystal structure of N-terminally truncated mature endoNF shows that the homotrimeric enzyme comprises a triple β-helix involved in substrate recognition 7 . This triple β-helix and the related triple-β-spiral motif have been identified in various proteins, which often play a role as virulence factors 8 .…”
Section: A R T I C L E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable structures include the triple β-helix regions of phage T4 gp12 (41) and gp5 (42), the K1F endosialidase (43) and endo-N-acetylneuramidase (29), streptococcal (pro)phage HylP1 and Hylp2 (44,45), the phage P22 cell penetrating needle gp26 (40), and phage Phi29 tail-spike (46). However, the most similar structures are those of phage P2 gpV (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other top structural homologs are the human UPF1 human helicase core (Z score ϭ 5.1, 1 st ) (21), the ␤-barrel domain of endo-alpha-sialidase (22), the tRNA-binding domain of the translation elongation factor Tu (23), and the receptor-binding domain of the avian reovirus fiber C (24). Of these top homologs, the endosialidase of bacteriophage K1F is most interesting due to its ability to bind sialic acid molecules, which are widely distributed in animal tissues and bacteria (22) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%